Hypothalamic–pituitary–adrenal function after subarachnoid haemorrhage - Jenkins, J. S. (1969)
In 18 patients with a ruptured aneurysm of the anterior communicating artery on the circle of Willis hypothalamuc–pituitary–adrenal function has been assessed by the diurnal variation in plasma cortisol levels and by the response to metyrapone, dexamethasone, and pyrogen. Eleven patients had an abnormal diurnal variation, seven had an abnormal response to metyrapone, and eight had an abnormal response to dexamethasone. All who were given pyrogen reacted normally to this stress. Two patients who died had lesions in the anterior hypothalamus, and it is suggested that this localization of lesions was responsible for the pattern of pituitary–adrenal dysfunction which was observed. An improvement in function was seen in many patients after an interval of a month.